2020
DOI: 10.1002/2211-5463.12867
|View full text |Cite
|
Sign up to set email alerts
|

Extended in vitro culture of primary human mesenchymal stem cells downregulates Brca1‐related genes and impairs DNA double‐strand break recognition

Abstract: Mesenchymal stem cells (MSCs) are multilineage adult stem cells with considerable potential for cell-based regenerative therapies. In vitro expansion changes their epigenetic and cellular properties, with a poorly understood impact on DNA damage response (DDR) and genome stability. We report here results of a transcriptome-based pathway analysis of in vitro-expanded human bone marrow-derived mesenchymal stem cell (hBM-MSCs), supplemented with cellular assays focusing on DNA double-strand break (DSB) repair. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The PLCs employed in the present study exhibit a phenotype and biological properties that closely resemble that of MSC from other tissues ( 3 , 22 , 68 ). It is noteworthy that prior studies have reported the downregulation of components of the DNA damage response (DDR) and HRR pathways in MSC with time in culture ( 94 96 ). As such, it is possible that the PLCs used in the present study, having been first cultured by explant, then selected for c-kit, and finally expanded for gene modification, no longer expressed sufficient levels of some of the key players in the HRR pathway required for efficient CRISPR/Cas9 gene-editing to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The PLCs employed in the present study exhibit a phenotype and biological properties that closely resemble that of MSC from other tissues ( 3 , 22 , 68 ). It is noteworthy that prior studies have reported the downregulation of components of the DNA damage response (DDR) and HRR pathways in MSC with time in culture ( 94 96 ). As such, it is possible that the PLCs used in the present study, having been first cultured by explant, then selected for c-kit, and finally expanded for gene modification, no longer expressed sufficient levels of some of the key players in the HRR pathway required for efficient CRISPR/Cas9 gene-editing to occur.…”
Section: Discussionmentioning
confidence: 99%
“…MM-UC-MSCs are expected to be a safer agent than cultured MSCs, embryonic stem cells, and induced pluripotent stem cells in vivo because minimally manipulated MSCs have little tumorigenicity, genetic mutations, and aging-related modifications[ 33 , 36 , 37 ]. As expected, we did not observe any immune rejection despite the allogeneic transplantation because MSCs have immunomodulatory properties[ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive in vitro culture induces the activation of a DNA damage response altering the functional properties of MSCs. This is mainly due to the accumulation of ROS associated with the oxidative metabolism of cultured cells and to the downregulation of genes involved in DNA repairing ( Bao et al, 2020 ). Indeed, a decrease in the number of repairing γH2AX/53BP1 DSB repair foci was observed in long-term culture of MSCs, in addition to a slower DNA repair kinetics, and an increased number of residual DNA double-strand breaks 7 h post irradiation.…”
Section: Discussion: Challenges and Perspectives For Mesenchymal Stromal Cells In The Context Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%